2018
DOI: 10.1016/j.ejso.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Wire localization of clip-marked axillary lymph nodes in breast cancer patients treated with primary systemic therapy

Abstract: Ultrasound-guided wire localization of the target lymph node is not suitable for clinical practice because of limitations regarding clip visibility and selective surgical preparation of the target lymph node. Further prospective evaluation of alternative techniques is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 25 publications
2
63
0
7
Order By: Relevance
“…We faced a challenge in US-guided dual-localization technique suggested in this study. Although clips were easily placed in all cases, without significant complications, 21% of clips were not clearly visible on US performed after NAC, as demonstrated previously in several studies [21, 35]. Although the hyperechoic (metallic) clip is easily visible against the background hypoechoic cortex of the axillary node before NAC, the cortex becomes thinner as NAC proceeds, which hinders differentiating the clip from echogenic fat strands.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We faced a challenge in US-guided dual-localization technique suggested in this study. Although clips were easily placed in all cases, without significant complications, 21% of clips were not clearly visible on US performed after NAC, as demonstrated previously in several studies [21, 35]. Although the hyperechoic (metallic) clip is easily visible against the background hypoechoic cortex of the axillary node before NAC, the cortex becomes thinner as NAC proceeds, which hinders differentiating the clip from echogenic fat strands.…”
Section: Discussionmentioning
confidence: 70%
“…The National Cancer Comprehensive Network guidelines recommend clip placement before NAC, because CN biopsy along with SN biopsy reduces the FNR [20]. However, invisibility of CNs during surgery needs further localization technique with materials of iodine seed or wire [21]. Iodine seeds have been suggested by studies in the US and Netherlands, but they are not available in many other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate identification of the clip remained a crucial factor in determining the precise placement of the localizing agent or skin mark and hence the success of clipped node removal. However, ultrasound visibilities of clips in the axillary lymph nodes post‐NACT have been suboptimal with reported rates of 72%‐83.3% . This is because chemotherapy can cause shrinkage and fibrosis of the lymph nodes resulting in loss of hypoechogenicity of the lymph nodes upon ultrasound, which makes it challenging to identify the tiny clips against a background of echogenic fat.…”
Section: Discussionmentioning
confidence: 99%
“…The removal rate of SMART in our study was comparable to the rates reported for other localization agents. The radioactive seed, wire and tattooing techniques had a removal rate of nodes of 97%-100%, 6,20 71%-100%, 11,13,21,22 and 83%-100%, 16,17 respectively.…”
Section: Discussionmentioning
confidence: 99%